THE ATTITUDE OF UZBEK SCIENTISTS TO THE PROBLEM OF DEVELOPING THE PERCEPTION AND IMAGINATION OF VISUAL ART WORKS AMONG SCHOOLCHILDREN - G. R. Ostonova (Web of Journals Publishing, 2024)
This article discusses the attitude of Uzbek scientists to the problem of developing the perception and imagination of visual art works among schoolchildren.
Keywords: Visual arts, general secondary school, perception, imagination, students, teachers, art, creativity.